2000
DOI: 10.1108/09540910010347872
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of lead‐free wave soldering process

Abstract: Though lead‐free replacements for SnPb eutectic alloys for reflow, wave, and hand soldering have been developed, relatively little has been reported on practical experience of lead‐free wave soldering processes. In wave soldering, the interaction between the PCB, flux, solder alloy and processing equipment makes it desirable to develop the consumables and the wave soldering machine concurrently. A crossfunctional project team was formed and a lead‐free wave soldering process developed and validated through nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…During wave soldering processes the concentration of copper in the solder bath increases in time due to dissolution of copper from the printed circuit board (PCB) pads and component terminations. As was reported earlier (Forsten et al , 2000), copper contents above 1 percent were found to give primary Cu 6 Sn 5 intermetallic crystals in the bath, causing changes in alloy fluidity and resulting in increased bridging. The fluidity of a solder, reciprocal of viscosity, also has an influence on the wettability.…”
Section: Introductionsupporting
confidence: 76%
“…During wave soldering processes the concentration of copper in the solder bath increases in time due to dissolution of copper from the printed circuit board (PCB) pads and component terminations. As was reported earlier (Forsten et al , 2000), copper contents above 1 percent were found to give primary Cu 6 Sn 5 intermetallic crystals in the bath, causing changes in alloy fluidity and resulting in increased bridging. The fluidity of a solder, reciprocal of viscosity, also has an influence on the wettability.…”
Section: Introductionsupporting
confidence: 76%
“…Due to environmental and health concerns, efforts to replace conventional Sn-Pb eutectic solder with lead-free alternatives have begun. [1][2][3][4][5] Considering performance, reliability, cost, and resources, the Sn-Ag and Sn-Zn alloys have received the most attention. Compared with Sn-Ag solder, Sn-Zn solder has some advantages, such as low melting point (198°C), adequate mechanical strength, low cost, and abundant supply; thus its prospects for development are numerous, and it has great market potential.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance heating curve of cycle 2 attened around 450°C and revealed an almost constant speci c contact resistance around 30 µΩ•cm 2 until the end of the holding phase which lasted three hours at 520°C. The cooling phase of cycle 2, as well as the entire cycle 3, showed that the speci c contact resistance of the Cr/FM interface remained always below 40 µΩ•cm 2 . This suggests that oxygen, initially contained in the solder, was fully consumed after cycle 2 and that Cr oxide degradation was completed around 450°C during the heating phase of cycle 2.…”
Section: Resultsmentioning
confidence: 99%
“…Metals or alloys with a melting temperature below 300°C are classi ed among the low melting alloys [1]. Multiple applications require the use of these low melting alloys, e. g. wave soldering [2] or characterization techniques, such as the Combined Thermoelectric Measurement technique (CTEM) [3]. Liquid metals represent a corrosive environment; however, unlike corrosion by aqueous solution involving electro-chemical processes, corrosion by liquid metal relies on a physical-chemical process which is independent of electron transfer through the liquid.…”
Section: Introductionmentioning
confidence: 99%